Pengaruh Keterampilan Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan di PT Sat Nusapersada Tbk - Arlina Zega; Riki Riki (Universitas 45 Surabaya, 2025)
This study aims to determine the effect of work skills and work environment on employee performance at PT. Satnusa Persada Tbk. The type of research used is a quantitative approach with a survey method, namely This research is included as an associative study. Associative research is a study that seeks the relationship or influence of independent variables of skills (X1), work environment (X2), and employee performance (Y) as dependent variables. The population of this study is all employees at PT. Satnusa Persada Tbk. The technique used in this study is purposive sampling. Definition of purposive sampling method